2016
DOI: 10.25268/bimc.invemar.1999.28.0.318
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Diets on Length and Biomass Production of Brine Shrimp Artemia Franciscana (Kellog, 1906)

Abstract: Total length and biomass production of the brine shrimp Artemia franciscana were studied fed on soybean and wheat micropulverized meals (applied alone or mixed at different proportions), live microalgae (Tetraselmis suecica and Chaetoceros calcitrans), and dried Spirulina as diets. Eight diets were tested in triplicates during 10 days. Significant differences (P < 0.05) were observed from day 1 onwards. The mixed meal-based diets showed better production results. At day 1, the Artemia nauplii fed on the 70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Feeding with soybean flour causes a low survival rate, because the flour particle size is too large, so it settles at the bottom of the tank, which pollutes the water [34] . Feed particles that attach to the tank will deteriorate the water quality due to accumulation of the hazardous gases such as nitrite [26,35] . Factors that influence the growth of Artemia include Artemia strain, nutritional content of feed and water quality, especially temperature and salinity [1,36,37] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feeding with soybean flour causes a low survival rate, because the flour particle size is too large, so it settles at the bottom of the tank, which pollutes the water [34] . Feed particles that attach to the tank will deteriorate the water quality due to accumulation of the hazardous gases such as nitrite [26,35] . Factors that influence the growth of Artemia include Artemia strain, nutritional content of feed and water quality, especially temperature and salinity [1,36,37] .…”
Section: Discussionmentioning
confidence: 99%
“…According to Saharan & Jood [24] , spirulina powder contains 71.90% protein, 1.27% lipid, and 13.63% carbohydrates, whereas Qaranjiki and Kırkağaç [25] found that nutrition content of spirulina powder including protein, lipid, and carbohydrate were 60.94%, 4.57%, and 28.07% respectively. Spirulina powder was also used as feed ingredients in several Artemia rearing studies [26,27,28] . Soybeans (Glycine max) belonging to the family leguminosae that grows in tropical and subtropical regions, and one of the world's most important sources of protein [29] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…did not follow a pattern, requiring further evaluation to determine the cause of its low dry weight. Other authors suggest that energy content of these species of microalgae can affect the growth of Artemia (García-Ulloa et al, 1999;Godinez et al, 2004).…”
Section: Discussionmentioning
confidence: 99%